The Effects of the Ramadan Month of Fasting on Disease Activity in Patients with Rheumatoid Arthritis - Mohd Shahrir Mohamed SAID,; Su Xu VIN,; Nashrah Adi AZHAR,; Yew JEANS,; Muhammad Nur Hafiz ABDULLAH,; Sakthiswary RAJALINGHAM,; Sazliyana SYAHRUL, (Archives of Rheumatology, 2013)
Objectives: This study aims to investigate possible effects of Ramadan month of fasting on disease activity in rheumatoid arthritis (RA) patients. Patients and methods: Between January 2010 and December 2011, 71 patients with RA who were scheduled for follow-up visit before Ramadan month and at two months after Ramadan month were retrospectively analyzed. The fasting cohort (n=39) and non-fasting cohort (n=32) were compared using the Disease Activity score 28 (DAS 28) and the patients' dietary habits both before and during Ramadan month. Results: In the fasting group, the mean DAS 28 score before Ramadan month was higher than for afterwards, however, this was not statistically significant (p>0.05). Clinical symptoms of morning stiffness and fatigue were found in fewer patients after Ramadan month, however, it was not statistically significant (p>0.05). There was a statistically significant reduction in morning stiffness (p=0.001) and functional class (p=0.011) after Ramadan in the fasting group. The intake of high-calorie foods was not statistically significant (p=0.022) in this group. Conclusion: Fasting lowers the mean DAS 28 in RA patients. Furthermore, dietary changes do not significantly affect RA disease activity in fasting patients.